The potential of fruit ethanolic extract Etlingera hemisphaerica as a solution for hyperglycemia, uremia, and hypercreatininemia in mice (Mus musculus) - Aceng Ruyani; Emi Suswati; Dhea Prita Pratiwi; Rina Elvia; Oktoviani Oktoviani; Deni Parlindungan (Open Veterinary Journal)
Background: Leaf ethanolic extract of Etlingera hemisphaerica (LE3H) has the potential to restore glucose, triglyceride, uric acid disorders, and reduce mercury toxicity. High levels of glucose (hyperglycemia), urine (uremia), and creatinine (hypercreatininemia) in the blood cause real health problems. Meanwhile, the phytochemical content in fruit ethanolic extract of E. hemisphaerica (FE3H) is higher than LE3H.